2017
DOI: 10.1186/s40942-016-0057-4
|View full text |Cite
|
Sign up to set email alerts
|

Arboviruses and the eye

Abstract: Arthropod-borne viruses, or arboviruses, are viruses that are transmitted through the bites of mosquitoes and ticks. There are numerous arboviruses throughout the world capable of causing human disease spanning different viral families and genera. Recently, dengue, chikungunya, and zika viruses have emerged as increasingly important arboviruses that can cause human disease, however no specific treatment or vaccine is available for them. In addition, ocular manifestations of these diseases have become more prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 44 publications
0
29
0
11
Order By: Relevance
“…Although eyes are sequestered from the systemic circulation, numerous viruses, among them arboviruses can still reach this organ and cause inflammation and pathologies [50]. Several flaviviruses, including DENV, ZIKV and WNV, have been described as triggering ophthalmic damage, including retinopathy [51]. Using a RT-qPCR approach, we observed that USUV could replicate in the eyes of neonatal mice (4x10 4 TCID50 eq per g, Fig 2B) and Ifnar -/infected mice (10 5 TCID50 eq per g).…”
Section: Usuv Induces Inflammatory Responses In the Eye And Efficientmentioning
confidence: 99%
See 1 more Smart Citation
“…Although eyes are sequestered from the systemic circulation, numerous viruses, among them arboviruses can still reach this organ and cause inflammation and pathologies [50]. Several flaviviruses, including DENV, ZIKV and WNV, have been described as triggering ophthalmic damage, including retinopathy [51]. Using a RT-qPCR approach, we observed that USUV could replicate in the eyes of neonatal mice (4x10 4 TCID50 eq per g, Fig 2B) and Ifnar -/infected mice (10 5 TCID50 eq per g).…”
Section: Usuv Induces Inflammatory Responses In the Eye And Efficientmentioning
confidence: 99%
“…It thus represents a powerful tool to study the pathophysiology of the RPE. Anatomically and developmentally, the eyes are known as an extension of the CNS and are proposed to act as a reservoir of viral replication; moreover RPE are known to be targeted by numerous pathogens including arboviruses, such as DENV, ZIKV and WNV, leading to major ophthalmological damage [50,51,56,76]. Numerous studies have shown the critical role of immune cells in retinal disease, and neuroinflammation is an important aspect of many diseases of the eye.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…It is very important that more extensive studies be carried out on the diagnosis and pathogenesis of arboviruses as some of them namely DFV, Zika virus and CHIKV infections have shown ocular manifestations which can be present at the time of fever or may manifest after many weeks. Anterior uveitis, optic neuritis and retinitis are the most common manifestations during the acute infection of these infections (de Andrade et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Ophthalmic presentations in arboviral infections in general are not common 10 . Intraocular involvement during WNV infection was fi rst described in 2003.…”
mentioning
confidence: 99%